International Trade, Flexible Manufacturing and Outsourcing - Carsten Eckel (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2005)
This study analyzes the impact of international trade on the diffusion of flexible manufacturing in a general equilibrium framework. Suppliers produce a flexible base product that can be adapted to the specific input requirements of a continuum of downstream industries. The vertical structure is determined by the trade-off between economies of scope in flexible manufacturing and product specificity of in-house production. In this framework, globalization can lead to alternating waves of insourcing and outsourcing, but once the world market reaches a threshold size, outsourcing prevails. We also derive a number of testable predictions with regard to firm size and productivity measures that are in line with recent empirical and casual evidence.
Keywords: L11; F12; L22; 330; International Trade; Flexible Manufacturing; Outsourcing; Vertical Integration; Globalization; General Equilibrium; Aussenwirtschaft; Flexibles Fertigungssystem; Lieferanten-Kunden-Beziehung; Outsourcing; Innovationsdiffusion; Globalisierung; Allgemeines Gleichgewicht; Theorie